(untitled) (Estudos em Design, 2023)
Abstract The user experience with products, services, and artifacts responds to different user needs and is affected by the design of the interface that mediates this interaction. In the context of digital interfaces, typography plays a significant role in the functionality and personality of the system, as actions and contents are conveyed to users through signs and symbols that inform and provide guidance and feedback. Given these relationships, this paper aimed to identify how different typographic properties are related to the satisfaction of user needs on user experience in digital interfaces. For that, a narrative literature review was conducted, followed by a systematization of the identified connections. As a result, it is proposed a diagram that presents the connections between five user needs – safety, functionality, usability, pleasurable experience, and individuation – and five properties of typography – accessibility, legibility, readability, personality, and customization – detailed in the context of the user experience in digital interfaces.